Medial and Lateral Canthal Reconstruction with an Orbicularis Oculi Myocutaneous Island Flap - Jihyeon Han; Sung Tack Kwon; Suk Wha Kim; Eui Cheol Jeong (Archives of Plastic Surgery, 2015)
Background The eyelid and canthal areas are common locations for cutaneous tumors. The medial canthus includes, among many other apparatuses, the canthal tendon and lacrimal canaliculi, and its characteristic thin and supple skin is hard to mimic and restore using tissue from other regions. Accordingly, reconstruction of the canthal area can prove challenging for surgeons. Although various methods, such as skin grafts and local flaps from adjacent regions, have been utilized for reconstructive purposes, they present known disadvantages. However, we were able to successfully reconstruct both lateral and medial canthal area defects by using orbicularis oculi myocutaneous island flaps. Methods Our study included seven patients who underwent medial or lateral canthal region reconstruction, using orbicularis oculi myocutaneous island flaps, between 2011 and 2014, following either cutaneous tumor excision or traumatic avulsion injury. Results Five patients had basal cell carcinoma, one had squamous cell carcinoma of the eyelid, and one had sustained a traumatic avulsion injury of the eyelid and canthal area. Entire flap loss was not observed in any patient, but one-a heavy smoker-showed partial flap loss, which healed with secondary intention and yielded acceptable results. Donor site morbidity was not observed, and all patients were satisfied with their surgical outcomes. Conclusions The canthal regions can be successfully reconstructed with orbicularis oculi myocutaneous island flaps. These flaps offer several key advantages, including similarity in texture, color, and thickness to the recipient site and a negligible incidence of donor site morbidity.